Effects of magnetic fields-stimulated 3D-Schwann cell-secreted extracellular vesicles regulate differentiation of neural stem cells and nerve regeneration - Yueh-Sheng Chen; Jian-Jr Lee; Yen-Hong Lin; Yun-Jhen Lin; Min-Hua Yu; Cheng-Yu Chen; Der-Yang Cho; Ming-You Shie (Materials & Design)
The nerve guide conduit is a favorable implant for repairing peripheral nerve injuries, which is vital for promoting nerve regeneration. Therefore, we integrated magnetic 3D Schwann cells (SC) into a 3D-printed nerve conduit made from polyurethane to establish an optimal microenvironment for neuron regeneration. The X-ray diffractometer and Fourier-transform infrared spectroscopy confirmed successful fabrication of a magnetic 3D cell block by incorporating iron oxide nanoparticles (IONP). The IONP-containing cell block, when exposed to static magnetic fields, exhibited enhanced cellular behavior, proliferation, and secretion of extracellular vesicles. Additionally, the nerve conduction was performed to evaluate the function of the regenerated nerves. These IONP-containing 3D cell block stimulated with the magnetic field exhibited higher nerve conduction velocity and reduced latency in the regenerated nerves. In vivo studies demonstrated an increased number and density of regenerated axons, along with more consistent and thicker myelin sheaths. The IONP and magnetic fields work synergistically to enhance the differentiation and proliferation of SC. This showcases their positive effect on promoting the regeneration of peripheral nerves after injuries.